2002
DOI: 10.1046/j.1523-1755.2002.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal flares in 91 SLE patients with diffuse proliferative glomerulonephritis

Abstract: Our results suggest that (a) a distinct subgroup of SLE patients exists, made up of younger patients with extensive, active lesions on renal biopsy, who are at higher risk for renal flares, (b) renal flares represent important predictors of doubling serum creatinine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 25 publications
10
47
0
8
Order By: Relevance
“…In the present study, 36% of the patients were African American, suggesting that, as expected, renal flare is an important risk factor for all patients with LN. Although the study by Moroni et al (1) found only nephritic flares to be significantly associated with poor renal outcomes, a more recent study of 91 Caucasian Systemic Lupus Erythematosus patients with proliferative LN found both nephritic and proteinuric flares to be associated with poor kidney outcomes (14), similar to our data. The recent EULAR guidelines emphasized nephritic flares.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, 36% of the patients were African American, suggesting that, as expected, renal flare is an important risk factor for all patients with LN. Although the study by Moroni et al (1) found only nephritic flares to be significantly associated with poor renal outcomes, a more recent study of 91 Caucasian Systemic Lupus Erythematosus patients with proliferative LN found both nephritic and proteinuric flares to be associated with poor kidney outcomes (14), similar to our data. The recent EULAR guidelines emphasized nephritic flares.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in agreement with prior lupus nephritis cohorts (27,28). Mosca et al found that nephritic flares and early proteinuric flares among adults were highly associated with doubling of serum creatinine (27,29). Similar findings have been reported in another adult cohort (28).…”
Section: Discussionsupporting
confidence: 87%
“…One aim of the study was to evaluate which of the two regimens offered better protection against renal flares, a factor that was associated strictly with long-term disease outcome (18,20). However, during the 4-yr follow-up, seven flares occurred in the cyclosporine group (10.6 flares/100 patient-years) and eight in the azathioprine group (13.4 flares/100 patientyears).…”
Section: Discussionmentioning
confidence: 99%